2010
DOI: 10.1245/s10434-010-1166-1
|View full text |Cite
|
Sign up to set email alerts
|

Extended Preoperative Chemotherapy Does Not Improve Pathologic Response and Increases Postoperative Liver Insufficiency After Hepatic Resection for Colorectal Liver Metastases

Abstract: Extended preoperative chemotherapy increases the risk of hepatotoxicity in CLM without improving the pathologic response. The type of chemotherapy (FOLFOX with bevacizumab) has more impact on pathologic response than the duration of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 233 publications
(130 citation statements)
references
References 20 publications
3
119
0
8
Order By: Relevance
“…[36] On the other hand Kishi et al, in a series of 219 patients who were treated pre-operatively with Oxaliplatin based chemotherapy, reported that SOS was present more frequently in those who received 9 or more cycles of chemotherapy than those who did not (42% vs. 26%; p=0.017). [57] Similarly the study of Aloia et al reported that the incidence of SOS in those receiving greater than 12 cycles of chemotherapy was 50% as compared to 25% in those receiving 6-12 cycles and 10% in those who received less than 6 cycles (p=0.01). [58] Several studies have undertaken multivariate analysis to identify independent risk factors associated with the development of chemotherapy induced liver injury.…”
Section: Clinical/biochemical Markers Of Chemotherapy Induced Liver Imentioning
confidence: 89%
“…[36] On the other hand Kishi et al, in a series of 219 patients who were treated pre-operatively with Oxaliplatin based chemotherapy, reported that SOS was present more frequently in those who received 9 or more cycles of chemotherapy than those who did not (42% vs. 26%; p=0.017). [57] Similarly the study of Aloia et al reported that the incidence of SOS in those receiving greater than 12 cycles of chemotherapy was 50% as compared to 25% in those receiving 6-12 cycles and 10% in those who received less than 6 cycles (p=0.01). [58] Several studies have undertaken multivariate analysis to identify independent risk factors associated with the development of chemotherapy induced liver injury.…”
Section: Clinical/biochemical Markers Of Chemotherapy Induced Liver Imentioning
confidence: 89%
“…Advantages of preoperative chemotherapy include: earlier treatment of micro-metastatic disease, determination of responsiveness to chemotherapy (which can be prognostic and help in planning postoperative management), and avoidance of local therapy for those patients with early disease progression (13).A meta-analysis of 27 studies including greater than 7200 patients found that patients with longer disease-free intervals; those, whose recurrences weresolitary, smaller, or unilobular; and those lacking extra-hepatic disease get more benefit from repeat hepatectomy (14).An important point to keep in mind is that irinotecan-and oxaliplatin-based chemotherapeutic regimens may cause liver steato-hepatitis and sinusoidal liver injury, respectively (15). In patients with initially unresectable disease when chemotherapy is planned, a surgical re-evaluation planned 2 months after initiation of chemotherapy to limit the development of hepatotoxicity, surgery should be performed as soon as possible after the patient becomes resectable (16).…”
Section: Discussion:-mentioning
confidence: 99%
“…It is therefore necessary to closely monitor tumor shrinkage (for example with a TC-scan every 8 weeks) and plan the timing of the resection to coincide with completion of the minimum number of chemotherapy courses required to achieve resectability, as it has been demonstrated that prolonged chemotherapy does not improve the pathologic response but just increases the risk of hepatotoxicity [92].…”
Section: What Happens During Systemic Treatment?mentioning
confidence: 99%